Are ambiguity aversion and ambiguity intolerance identical? A neuroeconomics investigation - Tanaka, Yusuke; Fujino, Junya; Ideno, Takashi; Okubo, Shigetaka; Takemura, Kazuhisa; Miyata, Jun; Kawada, Ryosaku; Fujimoto, Shinsuke; Kubota, Manabu; Sasamoto, Akihiko; Hirose, Kimito; Takeuchi, Hideaki; et al. (Frontiers in Psychology, 2015)
In recent years, there has been growing interest in understanding a person’s reaction to ambiguous situations, and two similar constructs related to ambiguity, “ambiguity aversion” and “ambiguity intolerance,” are defined in different disciplines. In the field of economic decision-making research, “ambiguity aversion” represents a preference for known risks relative to unknown risks. On the other hand, in clinical psychology, “ambiguity intolerance” describes the tendency to perceive ambiguous situations as undesirable. However, it remains unclear whether these two notions derived from different disciplines are identical or not. To clarify this issue, we combined an economic task, psychological questionnaires, and voxel-based morphometry (VBM) of structural brain magnetic resonance imaging (MRI) in a sample of healthy volunteers. The individual ambiguity aversion tendency parameter, as measured by our economic task, was negatively correlated with agreeableness scores on the self-reported version of the Revised NEO Personality Inventory. However, it was not correlated with scores of discomfort with ambiguity, one of the subscales of the Need for Closure Scale. Furthermore, the ambiguity aversion tendency parameter was negatively correlated with gray matter (GM) volume of areas in the lateral prefrontal cortex and parietal cortex, whereas ambiguity intolerance was not correlated with GM volume in any region. Our results suggest that ambiguity aversion, described in decision theory, may not necessarily be identical to ambiguity intolerance, referred in clinical psychology. Cautious applications of decision theory to clinical neuropsychiatry are recommended.